Performance metrics in public venture capital funds - Bielicki, Marcin (Mierniki efektywności wykorzystywane w publicznych funduszach venture capital, 2021)
Public venture capital funds are a unique type of financial intermediary. They pursue the goals, often conflicting, of public and private investors, which makes measuring their effectiveness a complex research challenge. This study aims to analyse the performance measurement methods used in public venture capital funds in Poland. For this purpose, in-depth interviews and a survey among managers of these entities were conducted. The study results show that the most significant emphasis is placed on financial efficiency, while non-financial determinants are mostly ignored. Considering the short history and lack of experience of many managers of public venture capital funds, this may further delay the process of development of this market.
Financial Sciences. Nauki o Finansach, 2021, vol. 26, no. 2, s. 1-17
Keywords: venture capital funds; effectiveness; performance measurement; fundusze venture capital; efektywność; pomiar efektywności